2021
DOI: 10.3390/microorganisms9122484
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends of Multidrug-Resistant (MDR) and Extensively Drug-Resistant (XDR) Salmonella Typhi in a Tertiary Care Hospital of Lahore, Pakistan

Abstract: Salmonella Typhi is a Gram-negative pathogen that causes typhoid fever in humans. The use of antibiotics to treat typhoid has considerably mitigated its fatality risk, but rising multidrug-resistant (MDR) and extensively drug-resistant (XDR) resistance in Pakistan threatens effective treatment. This study determined the prevalence of MDR and XDR S. Typhi at a local hospital in Lahore. Blood samples (n = 3000) were obtained and processed for bacterial identification. Antibiotic susceptibility test was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
5
27
0
Order By: Relevance
“…Several studies have documented the spread of MDR and XDR S . Typhi pathogens in Pakistan and other parts of the world with a travel history to Pakistan [ 7 , 13 15 , 29 ]. MDR and XDR S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented the spread of MDR and XDR S . Typhi pathogens in Pakistan and other parts of the world with a travel history to Pakistan [ 7 , 13 15 , 29 ]. MDR and XDR S .…”
Section: Discussionmentioning
confidence: 99%
“…Several S . Typhi pathogens are resistant to antibiotics normally recommended for the treatment of typhoid fever, including ampicillin, ceftriaxone, chloramphenicol, ciprofloxacin, and sulfamethoxazole/trimethoprim, and are only sensitive to azithromycin (oral antibiotic) and carbapenems (injectable antibiotic) [ 7 ]. However, even cases of azithromycin resistance have been reported from Bangladesh [ 8 ], Nepal [ 9 ], and India [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fearing its misuse in the current COVID-19 pandemic, acquiring a single resistance can change the treatment paradigm of typhoid fever from outpatient to hospitalization of every patient. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on Salmonella from Lahore, Pakistan only focus on epidemiology, antimicrobial susceptibility testing (AST), detection of ESBL and these are usually from single centers with a small number of samples 6 , 22 , 30 , 31 Here we extended our study with collection of samples from all the major tertiary care hospitals in Lahore. In addition to this we used standard broth microdilution method and E-strips for AST and all the 150 XDR S .…”
Section: Introductionmentioning
confidence: 99%
“…Terfassa et al in her study reported that 10% and 33.3% of the isolates of Salmonella and Shigella respectively were multi drug resistant ( 9 ). Another concerning fact was the emergence of XDR (Extensively drug resistant) Salmonella in Pakistan ( 10 ).…”
Section: Introductionmentioning
confidence: 99%